Co-processing of petcoke and producer gas obtained from RDF gasification in a white cement plant: A techno-economic analysis. (15th February 2023) - Sharma, Prateek; Sheth, Pratik N.; Mohapatra, B.N.
Abstract: White cement production, unlike grey cement, depends entirely on ashless conventional fuels (oil, petcoke) to meet its thermal energy requirement. The primary barrier to utilizing any solid alternative fuel in white cement is the impact on whiteness due to ash content. The study is focused on establishing producer gas from refuse-derived fuel (RDF) gasification as an alternative fuel in clinker production in an Indian white cement plant with a 15% thermal substitution rate (TSR). A stoichiometric calciner model has been developed to predict calciner outlet parameters considering co-firing of petcoke and producer gas, where producer gas has a high heating value (HHV) of 3.95 MJ/Nm 3 and gas yield of 2.36 Nm 3 /kg RDF. The model predicted the decrease in calciner outlet temperature by 2.6% at 15% TSR with 8.49% CO2 mitigation potential by replacing conventional fuel. It is concluded that RDF gasification is viable for white cement plants considering an IRR of 13.57% and discounted payback period of six years and two months for a 10-year gasifier operation. The study will facilitate the utilization of the RDF in white cement plants, reducing their manufacturing cost and dependence on fossil fuels. Highlights: Integration of refuse derived fuel (RDF) gasification in a white cement plant. Producer gas from RDF gasification as an alternative fuel in a calciner. Prediction of calciner outlet parameters using a stoichiometric calciner model. Techno-economic analysis: 15% thermal substitution rate (TSR) using producer gas. IRR of 13.57% and a discounted payback period of six years two months.